De Conspiratione / О Заговоре: сборник монографий / [cост. А. И. Фурсов] - Фурсов Андрей Ильич
Экземпляры: КХ (20130927) / Инвентарный номер: 1092610 / Цена: / Сис.шифр: 66.4 / Авт.знак: D29 / ГРНТИ: 11 / ББК: 66.4(0)